Medical emergencies in rural North Queensland: Doctors perceptions of the training needs. (16th November 2018) - Pandit, Tarsh; Sabesan, Sabe; Ray, Robin A.
Abstract: Objective: This study aimed to explore doctors' perceptions of the training needs of rural doctors in the context of managing emergencies in rural North Queensland. Design: Using a qualitative approach, 20 semistructured interviews were conducted via telephone, video conference and in‐person. Using an interview guide, areas such as preparedness of junior doctors for rural practice, areas for further training and confidence with managing emergencies were discussed. Interviews were analysed using the principles of grounded theory. Participant recruitment continued until data saturation was achieved. Setting: Multiple health facilities across three hospital and health services in North Queensland. Participants: (i) Doctors with current or recent work in rural North Queensland; (ii) doctors involved with rural medical training; and (iii) emergency medicine specialists working in a tertiary referral centre. Main outcome measure: Perspectives of doctors on the training needs of rural doctors in North Queensland. Results: Rural doctors were found to be as prepared as they could be to take up rural practice; however, they still had training needs. Region‐specific emergencies, access to regular in‐house simulations and non‐medical challenges, including understanding local team dynamics and taking on a team leader role, were seen as key training needs. Senior doctors indicated that further formal and informal on‐the‐job training were required for provisional fellows with limited experience in the emergency department. Conclusion: Certain training needs of rural doctors still remain unmet. Further access to in‐house simulations and tele‐training could be useful strategies to meet these training needs to further support rural doctors.